PAX5 alterations in genetically unclassified childhood Precursor B‐cell acute lymphoblastic leukaemia. (26th June 2015) - Stasevich, Irina; Inglott, Sarah; Austin, Nicola; Chatters, Steve; Chalker, Jane; Addy, Dilys; Dryden, Carryl; Ancliff, Philip; Ford, Anthony; Williams, Owen; Kempski, Helena
Summary Here, we report a high incidence of PAX5 abnormalities observed in 32/68 (47%) of patients with genetically unclassified childhood precursor B‐cell acute lymphoblastic leukaemia (pre‐B ALL). Various deletions, gains, mutations and rearrangements of PAX5 comprised 45%, 12%, 29% and 14%, respectively, of the abnormalities found. 28% of patients showed more than one abnormality of the gene, implying bi‐allelic impairment of PAX5. Novel PAX5‐RHOXF2, PAX5‐ELK3 and PAX5‐CBFA2T2 rearrangements, which lead to aberrant expression of PAX5, were also identified. PAX5 rearrangements demonstrated a complex mechanism of formation including concurrent duplications/deletions of PAX5 and its partner genes. Finally, the splice variant c.1013‐2A>G, seen in two patients with loss of one PAX5 allele, was confirmed to be germ‐line in one patient and somatic in the other. PAX5 alterations were also found to be clinically associated with a higher white blood cell count (P = 0·015). These findings contribute to the knowledge of PAX5 alterations and their role in the pathogenesis of pre‐B ALL.